Construction of Color-Magnitude Diagrams Using Real Astronomical Data for Teaching at School - Hernandez-Silva, C; Montecinos-Barros, R; Fuentes-Morales, I (Institute of Physics, 2024)
In this paper, with the aim of bridging the gap between cutting-edge research and the classroom, we present a situated learning proposal to integrate astronomical data and tools in the teaching of mathematics and physics. Our approach focuses on the construction of magnitude-color diagrams for two well-known star clusters, the Pleiades and 47 Tucanae, which are visible from the southern hemisphere, using virtual observatory-based applications Aladin and Topcat, using Simbad data specifically to separate data differences due to proper motion and/or reddening due to absorption by interstellar dust. To assess the feasibility of implementing these tools at school, we organized a workshop for science teachers that received a positive response. In addition, we also discuss the limitations and challenges that could hinder the effective application of these tools for educational purposes. © 2024 European Physical Society.